2017
DOI: 10.1177/1099800417711583
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Stress in Young Children Using Hair Cortisol: The State of the Science

Abstract: Extensive literature suggests that adverse experiences in early childhood may deleteriously impact later health. These effects are thought to be related to the impact of persistent or chronic stress on various biological processes, mediated by dysregulation of the hypothalamic-pituitary-adrenal (HPA) axis, and ultimately irregularities in cortisol levels. Ameliorating persistent stress in young children requires accurately measuring the chronicity of physiologic stress, which is difficult in young children bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
81
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(84 citation statements)
references
References 82 publications
3
81
0
Order By: Relevance
“…Firstly, HCC is an indirect indicator of stress, and it assesses all exposure to cortisol. As has been stated, HCC has been found to be elevated in children from low SES families but also in children who have perceived poorer temperament or behavior (i.e., are more fearful or have socioemotional issues) [8]. Thus, research is still needed to clarify the role of the developing HPA axis in the level of HCC as well as the role of elevated HCC in response to potential stress exposures in young children.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, HCC is an indirect indicator of stress, and it assesses all exposure to cortisol. As has been stated, HCC has been found to be elevated in children from low SES families but also in children who have perceived poorer temperament or behavior (i.e., are more fearful or have socioemotional issues) [8]. Thus, research is still needed to clarify the role of the developing HPA axis in the level of HCC as well as the role of elevated HCC in response to potential stress exposures in young children.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…The strengths of the current study include a relatively large sample of children, objective assessment of long-term stress, and validated assessment of temperament. Although assessing HCC in young children is somewhat new, it has been recognized as a valuable tool in research [8,27]. The use of daily ST diaries with open questions instead of ready-given response categories in assessing ST was chosen to increase the representativeness of ST.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Although proxy‐reported data can be collected for young children, discrepancies exist between self‐reported and proxy‐reported data because of parents or legal guardians expressing their own perceptions of stress instead of their children's perceptions when the latter method is used 12 . Because of these limitations of self‐reported or proxy‐reported stress, hair cortisol concentration (HCC) has emerged as a promising objective biomarker of chronic stress in children, especially among those who are young 13 . Cortisol is released during acute stress due to activation of the hypothalamic pituitary adrenal (HPA) axis.…”
Section: Introductionmentioning
confidence: 99%
“…No study to date has examined relationships between HCC and more specific indices of childhood disadvantage, such as income poverty (i.e., family income below the poverty line) and social exclusion (i.e., experience of disadvantage in multiple domains, including economic and social), and particularly in a low‐income population. A recent review of HCC as a measure of stress in children identified these issues (and others) as important next steps for research in this area (Bates, Salsberry, & Ford, ).…”
Section: Introductionmentioning
confidence: 99%